Independent – Interdependent Self Construal pada Mahasiswa Kota Bandung - Herkyles Surya Fadilah; Dewi Rosiana (Bandung Conference Series: Psychology Science, 2024)
Abstract. This study aims to comprehensively explore Self-Construal among university students in Bandung, considering their ethnic and cultural backgrounds. Comparisons of students' self-construal can influence whether they behave according to personal desires or follow academic demands. This study employs a mixed-methods approach with a sequential explanatory strategy (quantitative-qualitative-interpretation of both findings). The measuring instrument used is the Self-Construal Scale (SCS) (n = 24) which measures two dimensions, namely independent (0.88) and interdependent self-construal (0.89), as well as semi-structured questions. There were 276 respondents in the quantitative study and 10 subjects in the qualitative study, representing cultural variations including Sundanese, Makassarese, Javanese, and Betawi. Two main conclusions were drawn. First, Self-Construal among students showed significant differences regardless of ethnicity for each student. Second, when viewed by ethnicity, there were no significant differences among students. The qualitative findings indicate that most students follow the majority cultural group in the expectations of the academic environment, but have different values in viewing themselves and interpersonal dependence based on various situations. Cultural differences can influence students' self-perception of the diverse academic environment, affecting their social and intercultural skills. Abstrak. Penelitian ini bertujuan untuk mengeksplorasi Self Construal secara komprehensif pada mahasiswa Kota Bandung dengan memperhatikan latar belakang etnis budaya. Perbandingan self-construal mahasiswa dapat memengaruhi apakah mereka berprilaku sesuai keinginan pribadi atau mengikuti tuntutan akademik. Penelitian ini menggunakan pendekatan mix metode dengan model sequential explanatory strategy (kuantitatif-kualitatif-inteprestasi kedua temuan). Alat ukur yang digunakan adalah Self-construal Scale (SCS) (n = 24) yang mengukur dua dimensi, yaitu independent (0,88) dan interdependent self-construal (0,89), serta pertanyaan semi-terstruktur. Terdapat 276 responden dalam studi kuantitatif dan 10 subjek dalam studi kualitatif, mewakili variasi budaya termasuk suku Sunda, Makasar, Jawa, dan Betawi. Menghasilkan dua kesimpulan utama. Pertama, Self Construal pada mahasiswa menunjukan perbedaan signifikan tanpa melihat kesukuannya pada setiap mahasiswa. Kedua, melihat pada kesukuannya menunjukan tidak ada perbedaan signifikan pada setiap mahasiswa. Temuan kualitatif menunjukkan bahwa sebagian besar mahasiswa mengikuti suku budaya mayoritas dalam harapan lingkungan perkuliahan, namun memiliki nilai yang berbeda dalam melihat diri dan ketergantungan interpersonal berdasarkan situasi yang beragam. Perbedaan budaya dapat memengaruhi pandangan diri mahasiswa terhadap lingkungan perkuliahan yang beragam, memengaruhi keterampilan sosial dan interkultural mereka.